2023
DOI: 10.1371/journal.pone.0281170
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mycobacteria proliferation in macrophages by low cisplatin concentration through phosphorylated p53-related apoptosis pathway

Abstract: Background Drug resistance is a prominent problem in the treatment of tuberculosis, so it is urgent to develop new anti- tuberculosis drugs. Here, we investigated the effects and mechanisms of cisplatin (DDP) on intracellular Mycobacterium smegmatis to tap the therapeutic potential of DDP in mycobacterial infection. Results Macrophages infected with Mycobacterium smegmatis were treated with DDP alone or combined with isoniazid or rifampicin. The results showed that the bacterial count in macrophages decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
0
0
Order By: Relevance
“…Macrophages are essential to the maintenance of the organism homeostasis, immunological control, and pathogen defense (10). Previous studies have confirmed that macrophages apoptosis is a risk factor for lipid metabolism diseases by controlling proliferation (11), lipoprotein efferocytosis and the release of proinflammatory cytokines (12,13). Oxidized low-density lipoprotein, cholesterol and fatty acid can all induce apoptosis of macrophages, leading to the acceleration of immunometabolism response.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages are essential to the maintenance of the organism homeostasis, immunological control, and pathogen defense (10). Previous studies have confirmed that macrophages apoptosis is a risk factor for lipid metabolism diseases by controlling proliferation (11), lipoprotein efferocytosis and the release of proinflammatory cytokines (12,13). Oxidized low-density lipoprotein, cholesterol and fatty acid can all induce apoptosis of macrophages, leading to the acceleration of immunometabolism response.…”
Section: Introductionmentioning
confidence: 99%